How can public works programmes create sustainable employment? - Esther Gehrke; Renate Hartwig (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
Public works (PW) programmes are long-standing development interventions that have become increasingly popular in recent years due to their potential `double dividend' of reducing poverty and fostering growth by transferring income directly to the poor, while at the same time building and improving the infrastructure and/or delivering other public goods and services. Originally used as tools for ad-hoc poverty relief in response to economic downturns and natural disasters, they are now being used more and more as long-term social protection tools. As ambitions rise, so there are likely to be more trade-offs, however. Hence, the question this paper seeks to answer is whether PW programmes are fit to serve multiple objectives and how they should be designed in order to do so. We concentrate on the effects of PW programmes on sustainable employment, which should be a good proxy for their effects on poverty reduction and growth. Based on a review of the empirical evidence, we make the following recommendations for the design of PW programmes: First, in order to promote productive investments and self-employment among beneficiaries, PW programmes need to generate sufficient employment in a reliable manner over a long period. Second, instead of aiming at skills development, PW programmes should deliver complementary services in the form of credit. Third, given that the majority of PW participants in rural areas are engaged in subsistence farming and agricultural wage labour, PW programmes should focus on the agricultural lean season. Fourth, PW programmes should set wages in such a way to promote that those most in need self-select into the programme. Fifth, PW programmes should concentrate on infrastructure projects that have a big impact on employment in the short and long term, such as projects designed to boost agricultural output and improve market access. Sixth, the community should be involved in the selection of projects in order to guarantee ownership, use and sustainability of the infrastructure generated.
Keywords: 330; Soziale Sicherung und Inklusion; Wirksamkeit und Evaluierung